Sen’s concept of development as freedom and the idea of sustainable development - Płachciak, Adam (Annales. Etyka w Życiu Gospodarczym, 2019)
On the one hand, the contemporary world is a place of sheer abundance; on the other, it is a place where the poverty is widespread, people’s needs are unsatisfied, and the natural and socioeconomic systems remain unstable. The negligence/absence of human rights and basic political needs pose a direct threat to development. One of the most effective answers to such a threat is the idea of sustainable development, which works towards the goal of satisfying the needs of present generations without depriving the future generations of their options and basic needs. Amartya Sen’s concept of development, understood as a process of extending basic civil rights and freedoms as well as improving the effectiveness of social security networks is crucial for intellectual reflection on the idea of sustainable development.